Proteomic analysis in allergy and intolerance to wheat products. (February 2011) - Mamone, Gianfranco; Picariello, Gianluca; Addeo, Francesco; Ferranti, Pasquale
Owing to its extensive use in the human diet, wheat is among the most common causes of food-related allergies and intolerances. Allergies to wheat are provoked by ingestion, inhalation or contact with either the soluble or the insoluble gluten proteins in wheat. Gluten proteins, and particularly the gliadin fraction, are also the main factor triggering celiac disease, a common enteropathy induced by ingestion of wheat gluten proteins and related prolamins from oat, rye and barley in genetically susceptible individuals. The role of gliadin and of its derived peptides in eliciting the adverse reactions in celiac disease are still far from being completely explained. Owing to its unique pathogenesis, celiac disease is widely investigated as a model immunogenetic disorder. The structural characterization of the injuring agents, the gluten proteins, assumes a particular significance in order to deepen the understanding of the events that trigger this and similar diseases at the molecular level. Recent developments in proteomics have provided an important contribution to the understanding of several basic aspects of wheat protein-related diseases. These include: the identification of gluten fractions and derived peptides involved in wheat allergy and intolerance, including celiac disease, and the elucidation of their mechanism of toxicity; the development and validation of sensitive and specific methods for detecting trace amounts of gluten proteins in gluten-free foods for intolerant patients; and the formulation of completely new substitute foods and ingredients to replace the gluten-based ones. In this article, the main aspects of current and prospective applications of mass spectrometry and proteomic technologies to the structural characterization of gluten proteins and derived peptides are critically presented, with a focus on issues related to their detection, identification and quantification, which are relevant to the biochemical, immunological and toxicological aspects of wheat intolerance.